Physical-chemical characterization of wheat flour, dough and bread (Revista de Investigaciones Universidad del Quindío, 2010)
The aim of this study was to evaluate some chemical components in a commercial wheat flour, dough and bread made. Whiteness index was determined on the wheat. Analysis of differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) test were conducted on bread and commercial wheat flour. To flour, bread and dough humidity tests, water activity (aw) and color determination were conducted. The results showed a significant color change of the dough (ÄE = 5.4191) and bread (ÄE = 12.7314) for the raw material (ÄE = 0), the results for humidity and water activity, were as expected compared with data found in literature. Other components evaluated were: determination of DSC and TGA to wheat flour which allowed the identification of structures that result from processing conditions like those generated during the glass transition, gelatinization and retrogradation of starch, as the thermal modifications by the combined treatments of heat and humidity, which change the physicochemical properties of starch without destroying its granular structure, also in the determination of DSC and TGA for bread, the glass transition is induced by the temperature change of an amorphous glassy polymer to a gradually rubbery state when it is heated
Keywords: Fortification; Physical-Chemical analysis; Wheat Flour; Food